TRANSFORMING HEALTHCARE DELIVERY: CONTRIBUTIONS FROM RADIOLOGICAL AND PHARMACEUTICAL TECHNICIANS IN SAUDI ARABIA - Abdulrahman Abdullah Alsadrani, RTR1, Abdullah Ali Halal Aalboyge, RTR1, Fahad Hamdi S Almutairi, PharmT2, Munif Ayad Al-Mutairi, PharmT2, Abdullah Mazloh Qanam Alenazi, PharmT2, Mishal Saud Al-Mutairi, PharmT2 (Chelonian Research Foundation, 2022)
Background: The healthcare sector in Saudi Arabia has been undergoing significant transformations to improve patient care and outcomes. Radiological and pharmaceutical technicians play a crucial role in this process, but their contributions have not been well-documented. This study aimed to explore the roles, challenges, and opportunities for radiological and pharmaceutical technicians in transforming healthcare delivery in Saudi Arabia. Methods: A mixed-methods approach was used, combining a cross-sectional survey and semi-structured interviews with radiological and pharmaceutical technicians working in various healthcare settings in Riyadh, Saudi Arabia. The survey assessed technicians' perceptions of their roles, job satisfaction, and barriers to effective practice. The interviews explored their experiences, challenges, and recommendations for improving healthcare delivery. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed using thematic analysis. Results: A total of 150 radiological and pharmaceutical technicians completed the survey (response rate: 75%), and 20 participated in the interviews. The majority of technicians reported high levels of job satisfaction (85%) and perceived their roles as essential in patient care (92%). However, they also identified several barriers to effective practice, including workload (78%), lack of professional development opportunities (65%), and limited interprofessional collaboration (60%). The interviews revealed themes related to the need for specialized training, the importance of technology adoption, and the value of patient-centered care. Technicians also highlighted the need for greater recognition and support from healthcare organizations and policymakers. Conclusion: Radiological and pharmaceutical technicians are key contributors to the transformation of healthcare delivery in Saudi Arabia. However, they face several challenges that need to be addressed through targeted interventions, such as specialized training, interprofessional collaboration, and technology adoption. Healthcare organizations and policymakers should recognize and support the vital roles of these technicians in improving patient care and outcomes. Further research is needed to evaluate the impact of these interventions on healthcare delivery and to explore the perspectives of other healthcare professionals and patients. Keywords: Healthcare delivery, radiological technicians, pharmaceutical technicians, interprofessional collaboration, patient-centered care, Saudi Arabia